Conductive composition
By using dimeric acid modified epoxy resin, low melting point alloy powder, silver-clad copper alloy powder, benzoxazine resin and reactive epoxy diluent in the conductive paste, the conductive paste was solved after hardening. The problems of insufficient heat resistance and the influence of curing shrinkage have achieved conductive compositions with low curing shrinkage and high heat resistance, which are suitable for electronic components.
Patent Information
- Application Number
- CN202411419726.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-21
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
AI Technical Summary
The existing conductive paste lacks heat resistance after hardening, and ignores the influence of curing shrinkage during hardening, resulting in defects such as warping and deformation of the cured substance at high temperatures.
By adjusting the dosage range of each component, the curing shrinkage rate is reduced by adjusting the amount range of each component and the curing shrinkage rate is reduced and Improve heat resistance and form a composition with conductive properties and good curing properties.
It achieves low curing shrinkage during the curing process and good heat resistance after hardening, avoiding the problem of warping and deformation of the cured substance at high temperatures, and improving the stability and durability of the conductive composition.
Smart Images

Figure BDA0005080418300000071
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive material comprising metal or alloy, and in particular to a conductive composition. Background Art
[0002] Taiwan Patent Publication No. TWI647711B discloses a conductive paste comprising: (A) a dimer acid-modified epoxy resin, and, relative to 100 parts by mass of (B) a low melting point metal powder having a melting point of 240°C or less, 200 to 1900 parts by mass of (B) a low melting point metal powder having a melting point of 240°C or less, 400 to 2200 parts by mass of (C) a high melting point metal powder having a melting point of 800°C or more containing a silver-coated copper alloy powder, 1.0 to 20.0 parts by mass of (D) a hardener containing a hydroxyl-containing aromatic compound, and 5.0 to 100.0 parts by mass of (E) a flux containing a polycarboxylic acid.
[0003] However, the applicant found that the heat resistance of the conductive paste of the Taiwan patent still has room for improvement after curing, and the influence of the curing shrinkage rate during the curing process is ignored. Summary of the invention
[0004] Therefore, an object of the present invention is to provide a conductive composition having low curing shrinkage during curing and better heat resistance after curing.
[0005] Therefore, the conductive composition of the present invention comprises a dimer acid modified epoxy resin, a low melting point alloy powder having a melting point range of 240° C. or less, a silver-coated copper alloy powder having a melting point range of 800° C. or more, a benzoxazine resin having a viscosity range of 100 cps to 400 cps at 25° C., and a reactive epoxy diluent. Based on 100 parts by weight of the dimer acid modified epoxy resin, the low melting point alloy powder is used in an amount ranging from 1800 parts by weight to 2200 parts by weight, the silver-coated copper alloy powder is used in an amount ranging from 1100 parts by weight to 1500 parts by weight, the benzoxazine resin is used in an amount ranging from 35 parts by weight to 175 parts by weight, and the reactive epoxy diluent is used in an amount ranging from 30 parts by weight to 70 parts by weight.
[0006] In the conductive composition of the present invention, the dimer acid-modified epoxy resin is at least one selected from the group consisting of dimer acid-modified bisphenol A epoxy resin, dimer acid-modified bisphenol F epoxy resin, dimer acid-modified bisphenol A / F epoxy resin, dimer acid-modified alicyclic epoxy resin, dimer acid-modified heterocyclic epoxy resin and dimer acid-modified novolac epoxy resin.
[0007] In the conductive composition of the present invention, the low melting point alloy powder is at least one selected from the group consisting of tin alloy powder, bismuth alloy powder and antimony alloy powder.
[0008] In the conductive composition of the present invention, the reactive epoxy diluent is a long carbon chain epoxy compound.
[0009] The conductive composition of the present invention further comprises a polyacid resin. Based on 100 parts by weight of the dimer acid-modified epoxy resin, the amount of the polyacid resin is in the range of greater than 0 parts by weight and less than 155 parts by weight.
[0010] In the conductive composition of the present invention, the polyacid resin is a dibasic acid resin.
[0011] In the conductive composition of the present invention, based on 100 parts by weight of the dimer acid-modified epoxy resin, the amount of the polyacid resin ranges from 65 parts by weight to 155 parts by weight.
[0012] The conductive composition of the present invention does not contain a solvent.
[0013] The beneficial effect of the present invention is that, through the mutual coordination of the above-mentioned components and their usage ranges, the conductive composition has the advantages of low curing shrinkage during the curing process and good heat resistance after curing. DETAILED DESCRIPTION
[0014] The conductive composition of the present invention comprises a dimer acid modified epoxy resin, a low melting point alloy powder, a silver coated copper alloy powder, a benzoxazine resin and a reactive epoxy diluent. In certain embodiments, the conductive composition further comprises a polyacid resin.
[0015] Each component is described in further detail below.
[0016] The term "dimer acid modified epoxy resin" generally refers to epoxy resin modified by dimer acid, and the types of epoxy resins include, but are not limited to, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol A / F type epoxy resin, alicyclic epoxy resin, heterocyclic epoxy resin, or novolac epoxy resin. In certain embodiments, the dimer acid modified epoxy resin is selected from at least one of the group consisting of dimer acid modified bisphenol A type epoxy resin, dimer acid modified bisphenol F type epoxy resin, dimer acid modified bisphenol A / F type epoxy resin, dimer acid modified alicyclic epoxy resin, dimer acid modified heterocyclic epoxy resin, and dimer acid modified novolac epoxy resin. In an exemplary embodiment, the dimer acid modified epoxy resin is jER-871 manufactured by Mitsubishi Chemical.
[0017] The low melting point alloy powder plays the role of a conductive filler in the conductive composition. The types of the low melting point alloy powder are, for example, but not limited to, tin alloy powder, bismuth alloy powder, or antimony alloy powder. In some embodiments, the low melting point alloy powder is selected from at least one of the group consisting of tin alloy powder, bismuth alloy powder, and antimony alloy powder. In an exemplary embodiment, the low melting point alloy powder is tin alloy powder. The melting point range of the low melting point alloy powder is below 240°C. In some embodiments, the melting point range of the low melting point alloy powder is 150°C to 240°C. In an exemplary embodiment, the melting point of the low melting point alloy powder is 220°C. Based on 100 parts by weight of the dimer acid-modified epoxy resin, the amount of the low melting point alloy powder ranges from 1800 parts by weight to 2200 parts by weight.
[0018] The term "silver-coated copper alloy powder" refers to copper alloy powder coated with silver. The silver-coated copper alloy powder plays the role of a conductive filler in the conductive composition. The melting point range of the silver-coated copper alloy powder is above 800°C. In certain embodiments, the melting point range of the silver-coated copper alloy powder is 800°C to 1500°C. Based on 100 parts by weight of the dimer acid-modified epoxy resin, the amount of the silver-coated copper alloy powder ranges from 1100 parts by weight to 1500 parts by weight.
[0019] The benzoxazine resin plays the role of a curing agent in the conductive composition, and the benzoxazine resin has a viscosity range of 100 cps to 400 cps at 25°C. In an exemplary embodiment, the benzoxazine resin has a viscosity of 200 cps at 25°C. In addition, the benzoxazine resin is in a liquid state due to the above-mentioned characteristics and can also serve as a solvent in the conductive composition, so the conductive composition does not need to include an additional solvent. In some embodiments, the conductive composition does not contain a solvent. Based on 100 parts by weight of the dimer acid-modified epoxy resin, the amount of the benzoxazine resin ranges from 35 parts by weight to 175 parts by weight.
[0020] The role of the reactive epoxy diluent is to reduce the viscosity of the dimer acid modified epoxy resin and promote the crosslinking of the dimer acid modified epoxy resin and the benzoxazine resin. The type of the reactive epoxy diluent is, for example, but not limited to, a long carbon chain epoxy compound, and the type of the long carbon chain epoxy compound is, for example, but not limited to, 1,4-butanediol diglycidyl ether. In certain embodiments, the reactive epoxy diluent is a long carbon chain epoxy compound. In an exemplary embodiment, the reactive epoxy diluent is 1,4-butanediol diglycidyl ether. Based on the amount of the dimer acid modified epoxy resin as 100 parts by weight, the amount of the reactive epoxy diluent ranges from 30 parts by weight to 70 parts by weight.
[0021] The polyacid resin plays the role of a curing agent and a soldering flux in the conductive composition. The types of the polyacid resin include, but are not limited to, dibasic acid resins, and the types of the dibasic acid resin include, but are not limited to, aliphatic dibasic acid polyanhydride resins. In certain embodiments, the polyacid resin is a dibasic acid resin. In an exemplary embodiment, the polyacid resin is an aliphatic dibasic acid polyanhydride resin. Based on 100 parts by weight of the dimer acid-modified epoxy resin, the amount of the polyacid resin ranges from greater than 0 parts by weight to less than 155 parts by weight. In certain embodiments, based on 100 parts by weight of the dimer acid-modified epoxy resin, the amount of the polyacid resin ranges from 65 parts by weight to 155 parts by weight.
[0022] In the subsequent application of the conductive composition, the conductive composition can be heated to solidify the conductive composition to form a conductive solidified product, which is suitable for use in passive electronic components such as resistors, capacitors or inductors. During the heating process, at least the dimer acid-modified epoxy resin and the benzoxazine resin undergo a cross-linking reaction, the low-melting point alloy powder melts, and the silver-coated copper alloy powder melts. The heating conditions are not limited, for example, the heating temperature range is 200°C to 300°C.
[0023] The present invention will be further described with reference to the following examples, but it should be understood that the examples are only for illustration and should not be construed as limitations of the present invention.
[0024] <Examples 1 to 5 and Comparative Examples 1 to 2> Conductive Composition
[0025] The conductive composition is obtained by mixing and preparing the components as shown in Table 1. The specific types and sources of the components are as follows. Dimer acid modified epoxy resin (source: Mitsubishi Chemical Corporation and model number: jER-871; CAS no.: 68475-94-5). The low melting point alloy powder is specifically a tin alloy powder with a melting point of 220°C (source: Mitsui Mining & Trading Co., Ltd. and model number: SAC305). The benzoxazine resin is specifically a benzoxazine resin with a viscosity of 200 cps at 25°C. The reactive epoxy diluent is specifically 1,4-butanediol diglycidyl ether (source: NAGASE and model number: EX-214L). The polyacid resin is specifically an aliphatic dibasic acid polyanhydride resin (source: Okamura Oil and model number: IPU-22AH).
[0026] 〈Property Evaluation〉
[0027] The conductive compositions of Examples 1 to 5 and Comparative Examples 1 to 2 were evaluated for glass transition temperature, volume resistivity, density, curing shrinkage and heat resistance. For the sake of simplicity, the detection process of these property evaluations is described using the conductive composition of Example 1 as an example, and the remaining Examples and Comparative Examples are analyzed according to the same detection process, and the evaluation results are shown in Table 1.
[0028] [Glass transition temperature (abbreviated as Tg, unit is ℃)]
[0029] The conductive composition of Example 1 was heated at 280°C to cure the conductive composition to form a cured product. The cured product was placed in a thermomechanical analyzer (source: TA; model: TMA Q400) to test the glass transition temperature under the parameter conditions of a temperature range of 30°C to 300°C and a pressure of 0.01N. The industry generally requires that the glass transition temperature of the cured product be greater than 170°C so that the cured product has better heat resistance, moisture resistance and thermal expansion coefficient.
[0030] [Volume resistance (unit: Ω·cm)]
[0031] The conductive composition of Example 1 was heated at 280°C to cure the conductive composition to form a solidified product. The solidified product was tested for volume resistance using a microresistance meter. The industry generally requires that the volume resistance of the solidified product be less than 20×10 -5 Ω·cm, so that the cured product has better conductivity.
[0032] [Curing shrinkage (unit: %)]
[0033] The conductive composition of Example 1 was placed in a density cup at 25°C to measure the density, and the density of the conductive composition was obtained (see Table 1). The conductive composition of Example 1 was heated at 280°C to cure the conductive composition to form a solidified product, and then the solidified product was placed in a four-dimensional balance to measure the density, and the density of the solidified product was obtained.
[0034] The formula for calculating the curing shrinkage is as follows: curing shrinkage = (density of the cured product - density of the conductive component) / density of the cured product × 100%. Because a high curing shrinkage will cause defects such as warping and deformation in the cured product, the industry generally pursues a curing shrinkage of the conductive component as low as possible during the curing process.
[0035] [Heat resistance (in times)]
[0036] The conductive composition of Example 1 is heated at 280°C to cure the conductive composition to form a cured product. The cured product is placed in an SMT reflow oven that uses infrared rays to perform reflow and is reflowed at 260°C for 180 seconds. If the cured product does not have electrical abnormalities such as short circuits and open circuits after reflow, the cured product is repeatedly reflowed at the above temperature after cooling until electrical abnormalities such as short circuits and open circuits occur. The total number of times the cured product is reflowed indicates the heat resistance of the cured product. The greater the total number of times, the better the heat resistance, indicating that the conductive composition is less likely to have electrical abnormalities such as short circuits and open circuits after curing.
[0037] The conductive compositions of Example 3, Comparative Example 1 and Comparative Example 2 were evaluated for moisture absorption and room temperature viscosity stability. For the sake of clarity, the detection process of these property evaluations is described using the conductive composition of Example 3 as an example, and Comparative Examples 1 and Comparative Examples 2 are analyzed according to the same detection process, and the evaluation results are shown in Table 1.
[0038] [Moisture absorption rate (unit: %)]
[0039] The conductive composition of Example 3 is heated at 280°C to solidify the conductive composition to form a solidified product, and then the weight of the solidified product is weighed. Prepare a water bath and place it on a heating plate. Then, place the solidified product in the water bath. Set the temperature of the heating plate to 150°C to continuously heat the water bath for 2 hours so that the solidified product absorbs moisture to obtain a hygroscopic product, and then weigh the weight of the hygroscopic product. The calculation formula for the moisture absorption rate is as follows: Moisture absorption rate of solidified product = (weight of hygroscopic product - weight of solidified product) / weight of solidified product × 100%. The industry generally requires that the moisture absorption rate of solidified products must be less than 1%. The lower the moisture absorption rate of the solidified product, the less significant the effect of the moisture in the solidified product on its glass transition temperature, modulus, self-strength and bonding strength.
[0040] [Room temperature viscosity stability (in days)]
[0041] The conductive composition of Example 3 was continuously stirred at room temperature (25°C) at a rotation speed of 10 rpm. A viscometer (source: Brookfield; model: HBT-DV3+) was used to track the viscosity change of the conductive composition during the stirring process, and the total number of days of stirring when the amplitude of the viscosity change of the conductive composition exceeded 50% was recorded. The total number of days reflects the room temperature viscosity stability of the conductive composition. A greater total number of days means a better room temperature viscosity stability, which means that the conductive composition can be used for a longer time, that is, the workability of the conductive composition is better.
[0042] Table 1
[0043]
[0044] As can be seen from Table 1, the conductive compositions of Examples 1 to 5 have good curing shrinkage during curing and the cured products formed have good heat resistance. In addition, the cured product formed by the conductive composition of Example 3 also has good moisture absorption rate, and the conductive composition of Example 3 has good room temperature viscosity stability.
[0045] Comparing Comparative Examples 1 to 2 with Examples 1 to 5, the main difference in ingredients between the conductive compositions of Comparative Examples 1 to 2 and Examples 1 to 5 is that Comparative Examples 1 to 2 use phenolic curing agents, while Examples 1 to 5 use benzoxazine resins. The conductive compositions of Comparative Examples 1 to 2 have higher curing shrinkage during the curing process and the formed cured products have poor heat resistance, while the conductive compositions of Examples 1 to 5 have lower curing shrinkage during the curing process and the formed cured products have better heat resistance. In addition, the conductive compositions of Comparative Examples 1 and 2 have poor room temperature viscosity stability and the formed cured products have higher moisture absorption rates, while the conductive composition of Example 3 has higher room temperature viscosity stability and the formed cured products have lower moisture absorption rates.
[0046] In summary, the conductive composition of the present invention has good room temperature viscosity stability and is suitable for long-term operation by combining the benzoxazine resin with other components and the amount of each component. The conductive composition has a good curing shrinkage rate during the curing process and is not prone to defects such as warping and deformation after curing. The cured product formed by curing the conductive composition has good moisture absorption rate and heat resistance and is not prone to electrical abnormalities such as short circuit and open circuit, so the purpose of the present invention can be achieved.
[0047] However, the above is only an embodiment of the present invention and should not be used to limit the scope of the present invention. All simple equivalent changes and modifications made according to the claims and description of the present invention are still within the scope of the present invention.
Claims
1. A conductive composition, characterized in that Include: Dimer acid modified epoxy resin; Low melting point alloy powder, melting point range is below 240℃; Silver-coated copper alloy powder, melting point range above 800°C; benzoxazine resin having a viscosity at 25°C ranging from 100 cps to 400 cps; and Reactive epoxy diluents; And based on 100 parts by weight of the dimer acid-modified epoxy resin, the amount of the low melting point alloy powder ranges from 1800 parts by weight to 2200 parts by weight, the amount of the silver-coated copper alloy powder ranges from 1100 parts by weight to 1500 parts by weight, the amount of the benzoxazine resin ranges from 35 parts by weight to 175 parts by weight, and the amount of the reactive epoxy diluent ranges from 30 parts by weight to 70 parts by weight.
2. The conductive composition according to claim 1, wherein: The dimer acid modified epoxy resin is at least one selected from the group consisting of dimer acid modified bisphenol A epoxy resin, dimer acid modified bisphenol F epoxy resin, dimer acid modified bisphenol A / F epoxy resin, dimer acid modified alicyclic epoxy resin, dimer acid modified heterocyclic epoxy resin and dimer acid modified novolac epoxy resin.
3. The conductive composition according to claim 1, wherein: The low melting point alloy powder is at least one selected from the group consisting of tin alloy powder, bismuth alloy powder and antimony alloy powder.
4. The conductive composition according to claim 1, wherein: The reactive epoxy diluent is a long carbon chain epoxy compound.
5. The conductive composition according to any one of claims 1 to 4, characterized in that: The conductive composition further comprises a polyacid resin. Based on 100 parts by weight of the dimer acid-modified epoxy resin, the amount of the polyacid resin is greater than 0 parts by weight and less than 155 parts by weight.
6. The conductive composition according to claim 5, wherein: The polyacid resin is a dibasic acid resin.
7. The conductive composition according to claim 5, wherein: Based on 100 parts by weight of the dimer acid-modified epoxy resin, the amount of the polyacid resin ranges from 65 parts by weight to 155 parts by weight.
8. The conductive composition according to claim 1, wherein: The conductive composition does not contain a solvent.